The Public Service: Innovation, Public Service Mall, Improving Public Services, Cirebon Regency - Salsabila, Gina; Aviyanti, Salsa Billa Nur; Heryanto, Yanto (ann4publisher@gmail.com, 2025)
Background. The Public Service Mall (MPP) is an initiative aimed at promoting good governance in Indonesia by enhancing public service standards based on sound governance principles. The Cirebon Regency Government continues to implement various innovations through the Public Service Mall, managed by the Investment and Integrated One-Stop Service Agency (DPMPTSP), which provides both licensing and non-licensing services in one location for various public services from multiple agencies. Based on the above issues, the author employs Everett Rogers' theory of innovation characteristics as a framework for analyzing the innovation of the Public Service Mall in Cirebon Regency. There are several characteristics of innovation, as follows: (1) Relative Advantage, (2) Compatibility, (3) Complexity, (4) Trialability, and (5) Observability. Aims. This study aims to investigate the innovation of the Public Service Mall in Cirebon Regency at the DPMPTSP. Methods. The success of this study can be measured based on the application of relevant theories. The limitation in human resources has resulted in the number of visitors to the Public Service Mall not meeting the institution's expectations. Conclusion. This occurs due to the low public awareness of the Public Service Mall, leading many to be unaware of its existence. Implementation. The one-stop service provided by the Public Service Mall makes it easier for the community to access various public services in one place, in line with the principle of relative advantage in Everett Rogers' theory, which states that an innovation is more likely to be adopted if it is perceived as better than previous approaches or practices.